Potential involvement of the bone marrow in experimental Graves’ disease and thyroid eye disease - Gulbins, Anne; Horstmann, Mareike; Keitsch, Simone; Soddemann, Matthias; Wilker, Barbara; Wilson, Gregory C.; Zeidan, Ryan; Hammer, Gary D.; Daser, Anke; Bechrakis, Nikolaos E.; Görtz, Gina-Eva; Eckstein, Anja (Frontiers in Endocrinology, 2023)
Abstract Introduction Graves’ disease is an autoimmune disorder caused by auto-antibodies against the thyroid stimulating hormone receptor (TSHR). Overstimulation of the TSHR induces hyperthyroidism and thyroid eye disease (TED) as the most common extra thyroidal manifestation of Graves’ disease. In TED, the TSHR cross talks with the insulin-like growth factor 1 receptor (IGF-1R) in orbital fibroblasts leading to inflammation, deposition of hyaluronan and adipogenesis. The bone marrow may play an important role in autoimmune diseases, but its role in Graves’ disease and TED is unknown. Here, we investigated whether induction of experimental Graves’ disease and accompanying TED involves bone marrow activation and whether interference with IGF-1R signaling prevents this activation. Results Immunization of mice with TSHR resulted in an increase the numbers of CD4-positive T-lymphocytes (p <0.0001), which was normalized by linsitinib (p = 0.0029), an increase of CD19-positive B-lymphocytes (p= 0.0018), which was unaffected by linsitinib and a decrease of GR1-positive cells (p= 0.0038), which was prevented by linsitinib (p= 0.0027). In addition, we observed an increase of Sca-1 positive hematopietic stem cells (p= 0.0007) and of stromal cell-derived factor 1 (SDF-1) (p <0.0001) after immunization with TSHR which was prevented by linsitinib (Sca-1: p= 0.0008, SDF-1: p <0.0001). TSHR-immunization also resulted in upregulation of CCL-5, IL-6 and osteopontin (all p <0.0001) and a concomitant decrease of the immune-inhibitory cytokines IL-10 (p= 0.0064) and PGE2 (p <0.0001) in the bone marrow (all p <0.0001). Treatment with the IGF-1R antagonist linsitinib blocked these events (all p <0.0001). We further demonstrate a down-regulation of arginase-1 expression (p= 0.0005) in the bone marrow in TSHR immunized mice, with a concomitant increase of local arginine (p <0.0001). Linsitinib induces an upregulation of arginase-1 resulting in low arginase levels in the bone marrow. Reconstitution of arginine in bone marrow cells in vitro prevented immune-inhibition by linsitinib. Conclusion Collectively, these data indicate that the bone marrow is activated in experimental Graves’ disease and TED, which is prevented by linsitinib. Linsitinib-mediated immune-inhibition is mediated, at least in part, by arginase-1 up-regulation, consumption of arginine and thereby immune inhibition.